PENGARUH MANAJEMEN KOMUNIKASI TERHADAP KINERJA PROYEK KONSTRUKSI DI KOTA MALANG - Indah Ria Rizkiyah (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2021)
Abstract In a construction project, the most important factor for the smooth running of a job other than human resources is communication between the parties involved in the construction project, including consultants and contractors. The purpose of this study is to determine the communication factors that influence the implementation of construction projects on the performance of construction projects, analyze and prove the communication factors that influence the implementation of construction projects, determine the effect of performance reports, and determine the effect of administration on construction project performance. This research was conducted at a medium qualified contractor company in the city of Malang, from a sample calculation of 30 respondents, namely the project's internal parties. Field data measurement techniques. Questionnaire data processing using SPSS version 21 computer program. The results of this study are communication planning activities, information distribution activities, performance reporting activities, and administrative activities have a positive and significant effect on the performance of construction projects in the city of Malang. Keywords: Construction Project, Communication, and performance